ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON MUSLIM UNTUK MEMANFAATKAN PRODUK LEMBAGA KEUANGAN SYARI’AH - Aslikhah Rina (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
The purpose of this research is to know the factors that influence of Non Muslim to become an user in BMT Maslahah Tosari. This research used qualitative descriptive method with approach case studies on a natural background. Data was collected by three methods i.e. observation, interview and documentation.The result showed that (1) factors that affect people’s interest in using services financial institutions shari’ahare consumption, revenues, product/ types of saving, the location, service, communityawareness and promotion. (2) Economic factors being the dominant reason for Non Muslim to be the customer in BMT Maslahah Tosari. (3) Other factors to cause Non Muslim to be the customer in BMT Maslahah Tosari are personal factor and psychological factors.Keywords: Non Muslim Client, promotion, and products.